2017
DOI: 10.3906/sag-1601-179
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of cervical spinal angle in patients with acute and chronic neck pain

Abstract: Background/aim: Clinicians associate the changes in cervical lordosis with neck pain, but there is no clear consensus on this. We aimed to investigate the relationships of cervical angles, neck pain, disability, and the psychological status of the patients with acute and chronic neck pain.Materials and methods: A total of 110 patients with neck pain were included in this study. Demographic and clinical characteristics of the patients were recorded. The lordosis angle was determined by the posterior tangent met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…All the cervical lordosis angles showed non-significant correlations to the pain scores. The results of our study are comparable to a study carried out by Aşkin et al, 21 who found no correlation between acute and chronic neck pain and the orientation of the cervical vertebrae. A shared limitation between the current study and that of Aşkin et al is a small sample size, which may contribute toward the lack of significant correlation.…”
Section: Discussionsupporting
confidence: 90%
“…All the cervical lordosis angles showed non-significant correlations to the pain scores. The results of our study are comparable to a study carried out by Aşkin et al, 21 who found no correlation between acute and chronic neck pain and the orientation of the cervical vertebrae. A shared limitation between the current study and that of Aşkin et al is a small sample size, which may contribute toward the lack of significant correlation.…”
Section: Discussionsupporting
confidence: 90%
“…Pain and functional improvements were assessed using visual analogue scale (VAS) and neck disability index (NDI). 6 Measurement of Radiographic Parameters The radiographic film cassette was placed 72 inches from the tube, and radiographs were taken without magnification. Digital X-ray photographs were collected from the PACS method, which were used to collect orientation measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical spinal angle is the angle between the straight lines that connect the posterior edges of the C2 and C7 vertebrae, and in the normal case, it is between 31° and 40°. [39,40] In patients with CNP, the cervical spinal angle tends to decrease compared to acute, [41,42] and there is a significant relationship between neck pain and angle in the case of less than 20°. [43] In this trial, the cervical spinal angle of the baseline will be compared with that of 9W.…”
Section: Methodsmentioning
confidence: 99%